Enhanced natural killer activity and production of pro-inflammatory cytokines in mice selected for high acute inflammatory response (AIRmax) - Castoldi, Lindsey (Blackwell Science Inc, 2007)
Strains of mice with maximal and minimal acute inflammatory responsiveness (AIRmax and AIRmin, respectively) were developed through selective breeding based on their high- or low-acute inflammatory responsiveness. Previous reports have shown that AIRmax mice are more resistant to the development of a variety of tumours than AIRmin mice, including spontaneous metastasis of murine melanoma. Natural killer activity is involved in immunosurveillance against tumour development, so we analysed the number and activity of natural killer cells (CD49b(+)), T-lymphocyte subsets and in vitro cytokine production by spleen cells of normal AIRmax and AIRmin mice. Analysis of lymphocyte subsets by flow cytometry showed that AIRmax mice had a higher relative number of CD49b(+) cells than AIRmin mice, as well as cytolytic activity against Yac.1 target cells. The number of CD3(+) CD8(+) cells was also higher in AIRmax mice. These findings were associated with the ability of spleen cells from AIRmax mice in vitro to produce higher levels of the pro-inflammatory cytokines tumour necrosis factor-α, interleukin-12p40 and interferon-γ but not the anti-inflammatory interleukin-10. Taken together, our data suggest that the selective breeding to achieve the AIRmax and AIRmin strains was able to polarize the genes associated with cytotoxic activity, which can be responsible for the antitumour resistance observed in AIRmax mice.